Hermite–Hadamard type inequalities for co-ordinated convex and qausi-convex functions and their applications - Latif, Muhammad Amer; Rashid, Saima; Dragomir, Silvestru Sever; Chu, Yu-Ming (Journal of inequalities and applications, 2019)
In the article, we present several Hermite–Hadamard type inequalities for the co-ordinated convex and quasi-convex functions and give an application to the product of the moment of two continuous and independent random variables. Our results are generalizations of some earlier results. Additionally, an illustrative example on the probability distribution is given to support our results.